Evaluation of apparent diffusion coefficient in endometrial carcinoma compared to normal endometrium: a retrospective study - Easo, Anu Sarah; Anand, Rajeev; Issac, Mini (International Journal of Research in Medical Sciences, 2021)
Background: To determine whether diffusion-weighted imaging (DWI) with measurement of apparent diffusion coefficient (ADC) will help in differentiating endometrial cancer from normal endometrium and to determine whether the grades of endometrial cancer will show significant difference in ADC values. Methods: This is a retrospective study done in MOSC medical college hospital Kolencherry. on patients on whom preoperative MRI was done before hysterectomy. Cases from July 2017 to March 2021 were included. Study cases included 40 females with pathologically confirmed endometrial cancer and 30 females with pathologically proven normal endometrium in cases of uterine leiomyoma and cervical cancer. The exclusion criteria for the study were patients with endometrial cancer in whom surgery was not done within 2 weeks of MRI, patients who were treated with chemotherapy or radiotherapy before surgery, patients who had hydrometra or pyometra. Results: The mean ADC value (10−3 mm2/second) of endometrial cancer was 0.77±0.04, which was significantly lower (p<0.05) than that of normal endometrium (1.323±0.05). The ADC values of different grades of endometrial cancers did not show any statistically significant difference (p>0.05). Conclusions: Our study showed that ADC measurement can differentiate between normal endometrium and endometrial cancer. The ADC values of different grades of endometrial cancers did not show any statistically significant difference.